Tin-based perovskite thin film and preparation method thereof, tin-based perovskite solar cell
Patent Information
- Application Number
- CN202510541219.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-28
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]有鉴于此,为了解决上述提及的技术问题中的至少之一,本发明提供了一种锡基钙钛矿薄膜及其制备方法、锡基钙钛矿太阳能电池,以获得具有高稳定性的锡基钙钛矿太阳能电池,进而解决锡基钙钛矿太阳能电池的稳定性较差的问题
[0008]根据本发明上述实施例提供的锡基钙钛矿薄膜的制备方法,采用亚锡化合物配制锡基钙钛矿前驱体溶液,亚锡化合物提供足量的二价锡离子、以及与二价锡离子配合的阴离子,与二价锡离子匹配的阴离子可以部分或全部的保留在锡基钙钛矿晶格结构或晶界中,阴离子官能团与二价锡之间的络合可以增强锡基钙钛矿薄膜的抗氧化性和辐照耐受性,从而将该锡基钙钛矿薄膜作为吸光层应用于锡基钙钛矿太阳能电池能够提高太阳能电池稳定性。
Smart Images

Figure CN123022092A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of photovoltaic materials technology. At least one embodiment of this invention relates to a perovskite solar cell, and more particularly to a tin-based perovskite thin film and its preparation method, and a tin-based perovskite solar cell. Background Technology
[0002] Perovskite solar cells are third-generation solar cells that utilize metal halide semiconductor perovskite as the light-absorbing material. Due to their low raw material cost, relatively simple fabrication process, and excellent photoelectric conversion efficiency, they have attracted widespread international attention. After more than a decade of development, the photoelectric conversion efficiency of the most efficient single-junction lead-based perovskite solar cell has increased from the initial 3.8% to 27%.
[0003] However, current high-efficiency solar cells generally contain the heavy metal lead, which greatly limits the application scenarios of perovskite solar cells and hinders their industrialization. Therefore, tin-based perovskite solar cells, which replace lead ion sites with low-toxicity tin ions, have emerged. Both tin-based and lead-based perovskites are direct bandgap semiconductors, and their bandgap widths are closer to the theoretical optimal value for solar cells, thus exhibiting higher theoretical photoelectric conversion efficiency, making them the most promising lead-free perovskite candidates. However, the poor stability of tin-based perovskite solar cells limits the full realization of their excellent photoelectric physical properties. Summary of the Invention
[0004] In view of the above, in order to solve at least one of the aforementioned technical problems, the present invention provides a tin-based perovskite thin film and its preparation method, and a tin-based perovskite solar cell, so as to obtain a tin-based perovskite solar cell with high stability, thereby solving the problem of poor stability of tin-based perovskite solar cells.
[0005] According to one aspect of the present invention, a method for preparing a tin-based perovskite thin film is provided, comprising: dissolving tin-based perovskite powder in an organic solvent to prepare a tin-based perovskite precursor solution, wherein the tin-based perovskite powder contains a tin-containing compound; and coating the tin-based perovskite precursor solution into a film, and obtaining a tin-based perovskite thin film after annealing.
[0006] According to another aspect of the present invention, a tin-based perovskite thin film obtained by the above-described preparation method is provided.
[0007] According to another aspect of the present invention, a tin-based perovskite solar cell is provided, comprising a light-absorbing layer comprising the aforementioned tin-based perovskite thin film.
[0008] According to the method for preparing tin-based perovskite thin films provided in the above embodiments of the present invention, a tin-based perovskite precursor solution is prepared using a tin-based compound. The tin-based compound provides sufficient divalent tin ions and anions that coordinate with the divalent tin ions. The anions that coordinate with the divalent tin ions can be partially or completely retained in the tin-based perovskite lattice structure or grain boundaries. The complexation between the anionic functional groups and divalent tin can enhance the oxidation resistance and radiation tolerance of the tin-based perovskite thin film. Thus, applying the tin-based perovskite thin film as a light-absorbing layer to tin-based perovskite solar cells can improve the stability of the solar cells. Attached Figure Description
[0009] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings of the embodiments will be briefly described below. Obviously, the drawings described below only relate to some embodiments of the present invention and are not intended to limit the present invention.
[0010] Figure 1 A flowchart illustrating the method for preparing tin-based perovskite thin films according to embodiments of the present invention;
[0011] Figure 2 A cross-sectional schematic diagram of a tin-based perovskite solar cell provided in an embodiment of the present invention;
[0012] Figures 3A-3B The images show a comparison of the surface morphology of the tin-based perovskite thin film before and after irradiation, as provided in Comparative Example 1.
[0013] Figures 4A-4B These are comparative images of the surface morphology of the tin-based perovskite thin film before and after irradiation, as provided in Example 1 of the present invention.
[0014] Figure 5A XRD comparison images of tin-based perovskite films after being placed in air for different times, provided as Comparative Example 1;
[0015] Figure 5B This is a comparison of XRD patterns of tin-based perovskite films after being placed in air for different times, as provided in Embodiment 1 of the present invention.
[0016] Figure 6A Photoluminescence intensity decay of the tin-based perovskite film provided in Comparative Example 1 as it ages in air;
[0017] Figure 6B This is a graph showing the photoluminescence intensity decay of the tin-based perovskite thin film provided in Embodiment 1 of the present invention as it ages in air.
[0018] Figure 7 Figures (a) to (d) in the figure are comparison figures of XPS test results of the tin-based perovskite thin films provided in Comparative Example 1 and Example 1 of the present invention before and after irradiation.
[0019] Figure 8 This is an XPS test result image of the tin-based perovskite thin film provided in Example 1 of the present invention after irradiation;
[0020] Figure 9 A comparison chart showing the photoelectric conversion efficiency test results of the tin-based perovskite solar cells provided in Comparative Example 2 and Example 2 of the present invention;
[0021] Figure 10 A comparison chart showing the stability test results of the tin-based perovskite solar cells provided in Comparative Example 2 and Example 2 of the present invention; and
[0022] Figure 11 The graph shows a comparison of the photoelectric conversion efficiency test results of the tin-based perovskite solar cells provided in Comparative Example 2 and Examples 2-4 of the present invention.
[0023] Explanation of reference numerals in the attached figures:
[0024] 1-Substrate;
[0025] 2- Bottom electrode;
[0026] 3-First carrier transport layer;
[0027] 4-Absorption layer;
[0028] 5-Second carrier transport layer;
[0029] 6-Top electrode. Detailed Implementation
[0030] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments and the accompanying drawings. However, this invention can be implemented in different forms and should not be construed as limited to the embodiments set forth herein. Rather, these embodiments are provided to make the invention thorough and complete, and to fully convey the scope of the invention to those skilled in the art. In the accompanying drawings, for clarity, the dimensions and relative dimensions of layers and regions may be exaggerated, and the same reference numerals denote the same elements throughout.
[0031] The terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the invention. The terms “comprising,” “including,” etc., as used herein indicate the presence of the stated features, steps, operations, and / or components, but do not exclude the presence or addition of one or more other features, steps, operations, or components.
[0032] In related technologies, tin-based perovskite solar cells generally suffer from the critical problem of poor stability. The specific reason lies in the Sn component that constitutes tin-based perovskite. 2+ It is very easy to be oxidized to Sn 4+This leads to the aging and degradation of the tin-based perovskite thin film, which forms the core structure. Furthermore, research shows that irradiation conditions also accelerate the oxidation of divalent tin, resulting in a large number of tin and halogen vacancies within the tin-based perovskite. These problems mean that tin-based perovskite solar cells still have numerous defects, hindering the generation and extraction of photogenerated carriers, reducing the stability of perovskite solar cells, and significantly limiting the realization of the theoretically excellent photoelectric properties of tin-based perovskites.
[0033] In view of this, the present invention provides a tin-based perovskite thin film and its preparation method, and a tin-based perovskite solar cell, so as to obtain a tin-based perovskite solar cell with high stability.
[0034] Figure 1 A flowchart illustrating the preparation method of tin-based perovskite thin films provided in this embodiment of the invention.
[0035] According to an exemplary embodiment of the present invention, the present invention provides a method for preparing a tin-based perovskite thin film, referring to... Figure 1 As shown, it includes steps S1 to S2.
[0036] Step S1: Dissolve tin-based perovskite powder in an organic solvent to prepare a tin-based perovskite precursor solution, wherein the tin-based perovskite powder contains tin oxide compounds.
[0037] In embodiments of the present invention, the tin-based perovskite powder includes formamidinium hydroiodate (FAI), stannous iodide (SnI2), stannous fluoride (SnF2), and phenylethylamine bromide (PEABr).
[0038] In some embodiments, the molar ratio of FAI+PEABr, SnI2, and SnF2 is 1:1:(0~0.2), wherein the molar ratio of FAI and PEABr is (1:0)~(0.7:0.3).
[0039] In some embodiments, the molar ratio of FAI, PEABr, SnI2 and SnF2 can be, for example, 0.85:0.15:1:0.1.
[0040] In some embodiments, the organic solvent includes at least one selected from dimethylformamide (DMF), dimethyl sulfoxide (DMSO), N-methylpyrrolidone (NMP), and γ-butyrolactone (GBL). The organic solvent may include, for example, DMF and DMSO, wherein the volume ratio of DMF to DMSO may be, for example, 4:1.
[0041] In embodiments of the present invention, the preparation of the tin-based perovskite precursor solution includes: dissolving FAI, PEABr, SnI2, SnF2, and a tin-containing compound in an organic solvent at a temperature of 15-70°C to obtain the tin-based perovskite precursor solution; the temperature conditions can be, for example, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 60°C, or 70°C, but are not limited to these values. If the temperature is too high, the perovskite precursor solution is prone to complexation, resulting in poor film quality. If the temperature is too low, it is not conducive to the rapid preparation of the tin-based perovskite precursor solution. The tin-based perovskite precursor solution prepared by controlling the temperature conditions at 15-70°C can significantly improve the film formation effect.
[0042] In some embodiments, the stannous compound includes at least one selected from stannous thiocyanate, stannous sulfate, stannous oxalate, stannous acetate, stannous sulfide, stannous fluoroborate, stannous petrolate, and stannous octanoate. The stannous compound provides sufficient divalent tin ions and anions that coordinate with the divalent tin ions. The anions that coordinate with the divalent tin ions can be partially or completely retained in the tin-based perovskite lattice structure or grain boundaries. The complexation between the anionic functional groups and the divalent tin can inhibit the migration of halide ions in the tin-based perovskite under irradiation, thereby enhancing the oxidation resistance and radiation tolerance of the tin-based perovskite film.
[0043] The stannous compound can be, for example, stannous thiocyanate, stannous sulfate, or stannous oxalate. In experiments related to this invention, it was found that stannous thiocyanate can exist stably in air, exhibiting strong divalent tin complexation. The presence of non-spherical structures such as thiocyanate ions, oxalate ions, and sulfate ions can inhibit the migration of tin-based perovskite halide ions under irradiation, significantly reducing halogen site defects.
[0044] In some embodiments, the molar ratio of tin in the tin sub-compound to tin in the tin-based perovskite precursor solution is 0.01% to 10%; the preferred molar ratios are 5%, 6%, 7%, 8%, 9%, and 10%, but are not limited to these values. In related experiments of this invention, it was found that a tin sub-compound content exceeding 5% exhibits a significant antioxidant effect. However, in experiments with doping levels exceeding 10%, excessive tin sub-compound may lead to instability in the host perovskite lattice, resulting in a significant increase in the roughness and pinholes of the tin-based perovskite film, leading to poor film quality and consequently poor electrical performance of the tin-based perovskite solar cell formed using the tin-based perovskite film.
[0045] Step S2: Coat the tin-based perovskite precursor solution into a film, and then anneal it to obtain a tin-based perovskite thin film.
[0046] In some embodiments, the coating method includes spin coating, blade coating, or spray coating.
[0047] In some embodiments, the annealing temperature is 70°C to 100°C, and the annealing time is 10 min to 20 min. For example, annealing can be performed at 70°C for 10 min, 70°C for 15 min, 70°C for 20 min, 80°C for 10 min, 80°C for 15 min, 80°C for 20 min, 90°C for 10 min, or 100°C for 10 min, but is not limited to these values. During the annealing process, the solvent in the tin-based perovskite precursor solution evaporates. In the relevant experiments of this invention, it was found that excessively low annealing temperatures are detrimental to the perovskite crystallization process of some tin-containing compound anions, while excessively high annealing temperatures directly lead to the oxidative degradation of the tin-based perovskite film. Therefore, controlling the annealing temperature and annealing time within the above-mentioned ranges can yield tin-based perovskite films with high crystallinity.
[0048] According to an exemplary embodiment of the present invention, the present invention provides a tin-based perovskite thin film obtained by the above-described preparation method.
[0049] According to an embodiment of the present invention, a tin-based perovskite precursor solution is prepared using tin-based perovskite powder containing tin oxide compounds, which can replenish the Sn oxidized during the preparation and operation of tin-based perovskites. 2+ Passivating tin vacancy defects can also utilize the highly electronegative anions of tin sub-compounds, such as SCN. - BF4 - SO4 2- The complexation of divalent tin inhibits the degradation of tin-based perovskite under irradiation conditions, which is beneficial for preparing high-quality tin-based perovskite films.
[0050] According to an exemplary embodiment of the present invention, the present invention provides a tin-based perovskite solar cell, including a light-absorbing layer comprising the aforementioned tin-based perovskite thin film.
[0051] Figure 2 This is a cross-sectional schematic diagram of a tin-based perovskite solar cell provided in an embodiment of the present invention.
[0052] refer to Figure 2 As shown, a tin-based perovskite solar cell is disposed on a substrate 1. The tin-based perovskite solar cell includes a bottom electrode 2, a first carrier transport layer 3, an absorber layer 4, a second carrier transport layer 5, and a top electrode 6 stacked in sequence.
[0053] In some embodiments, the first carrier transport layer 3 may be poly(3,4-ethylenedioxythiophene) / polystyrene sulfonate (PEDOT:PSS).
[0054] In some embodiments, the second carrier transport layer 5 may be a fullerene derivative (ICBA).
[0055] In some embodiments, the top electrode 6 can be silver with a thickness of 80-120 nm.
[0056] In some embodiments, a barrier layer, such as copper bath (BCP), is further provided between the second carrier transport layer 5 and the top electrode 6.
[0057] The following illustrative description illustrates the designed tin-based perovskite thin film, its preparation method, and a tin-based perovskite solar cell. It should be noted that this illustration is merely a specific embodiment of the present invention and does not limit the scope of protection of the present invention.
[0058] Comparative Example 1
[0059] Prepare a 0.9 M FASnI3 tin-based perovskite precursor solution. Specifically, dissolve tin-based perovskite powder in an organic solvent, stir at room temperature (20°C) for 3 hours, and filter using a 0.22 μm PTFE filter. The tin-based perovskite powder comprises FAI, SnI2, and SnF2, with a molar ratio of 0.1:1:0.1. The organic solvent is a mixed solution of DMF and DMSO, with a volume ratio of V / V. DMF :V DMSO =4:1. The obtained tin-based perovskite precursor solution was spin-coated onto the substrate at a speed of 5000 r / min for 40 s. At the 25th s of spin-coating, 600 μL of chlorobenzene (CB) was added dropwise, and the substrate was annealed at 80 °C for 10 min to obtain a tin-based perovskite film.
[0060] The tin-based perovskite film prepared in Comparative Example 1 was irradiated in air for 5 min using a 405 nm laser. The morphology of the tin-based perovskite film before and after irradiation was measured using an electron microscope. The test results are as follows: Figures 3A-3B As shown.
[0061] Figures 3A-3B The images show a comparison of the surface morphology of the tin-based perovskite thin film before and after irradiation, as provided in Comparative Example 1.
[0062] refer to Figures 3A-3B As shown, the tin-based perovskite film provided in Comparative Example 1 has good crystal integrity before irradiation, but after irradiation, the tin-based perovskite film shows obvious grain degradation and generates a large number of pores.
[0063] Example 1
[0064] Tin-based perovskite films were prepared using the same method as in Comparative Example 1, except that the tin-based perovskite precursor solution also included Sn(SCN)2, and the Sn in Sn(SCN)2 was...2+ The molar ratio of the content of tin to the content of tin ions in the tin-based perovskite precursor solution is 10%.
[0065] Figures 4A-4B These are comparative images of the surface morphology of the tin-based perovskite thin film before and after irradiation, as provided in Example 1 of the present invention.
[0066] refer to Figures 4A-4B As shown, the tin-based perovskite film provided in Example 1 of this invention can still maintain good grain integrity after being irradiated for the same period as in Comparative Example 1. This indicates that a tin-based perovskite precursor solution containing tin sub-compounds can be used to prepare a tin-based perovskite film with high irradiation stability.
[0067] Figure 5A XRD comparison images of tin-based perovskite films after being placed in air for different times, provided as Comparative Example 1.
[0068] Figure 5B The XRD comparison images are of tin-based perovskite films after being placed in air for different times, as provided in Embodiment 1 of the present invention.
[0069] refer to Figure 5A , Figure 5B As shown, under the same aging conditions, the intensity of the (100) main peak of the tin-based perovskite film provided by Comparative Example 1 (control sample) decreased significantly after being placed in air for 5 min or 10 min; the tin-based perovskite film provided by Example 1 (experimental sample) of the present invention maintained a better crystallization intensity of the (100) main peak, which indicates that the addition of stannous compound stannous thiocyanate has a significant effect on improving the antioxidant properties of tin-based perovskite film.
[0070] Figure 6A Photoluminescence intensity decay diagram of the tin-based perovskite thin film provided in Comparative Example 1 as it ages in air.
[0071] Figure 6B This is a graph showing the attenuation of photoluminescence intensity of the tin-based perovskite thin film provided in Embodiment 1 of the present invention as it ages in air.
[0072] like Figure 6A , Figure 6BAs shown, tin-based perovskite films provided in Comparative Example 1 and Example 1 of the present invention were excited in air using a 405 nm laser, and the attenuation signal of their photoluminescence intensity was characterized in situ. The results show that the tin-based perovskite film of Example 1 (experimental sample) can maintain a high luminescence intensity for over 300 s, while the tin-based perovskite film of Comparative Example 1 (control sample) only maintained it for less than 170 s under the same test conditions. This fully demonstrates the significant role of adding the stannous compound stannous thiocyanate in suppressing non-radiative recombination in tin-based perovskites, reducing bulk defect density, and improving material stability.
[0073] Figure 7 Figures (a) to (d) are XPS test spectra of the tin-based perovskite thin films provided in Comparative Example 1 and Example 1 of the present invention before and after irradiation.
[0074] Figure 7 Figures (a) to (b) in the figure show the XPS spectra of the tin-based perovskite film of Comparative Example 1 before and after irradiation. Figure 7 Figures (c) to (d) in Table 1 show the XPS spectra of the tin-based perovskite thin film of Example 1 of the present invention before and after irradiation. Peak fitting was performed on the XPS spectra of the tin-based perovskite thin film of Comparative Example 1 and Example 1 of the present invention before and after irradiation, and the results are shown in Table 1.
[0075] Table 1
[0076]
[0077] refer to Figure 7 As shown in Figures (a) to (d) and Table 1, the Sn of the tin-based perovskite thin film provided in Example 1 of the present invention... 4+ The Sn content was lower than that of the tin-based perovskite film in Comparative Example 1 both before and after irradiation. 4+ Content, which indicates Sn 2+ Less oxidation occurs, which helps to reduce tin vacancies in tin-based perovskite films, reduce defects in tin-based perovskite films, and thus help to improve the photoelectric conversion efficiency of tin-based perovskite solar cells formed by tin-based perovskite films.
[0078] Figure 8 The XPS test spectrum of the tin-based perovskite thin film provided in Example 1 of the present invention after irradiation.
[0079] refer to Figure 8 As shown, the XPS test spectrum of the tin-based perovskite film of Example 1 of the present invention shows that the tin-based perovskite film of Example 1 of the present invention contains the element S in its crystal structure. This indicates that the anionic functional group of the tin suboxide compound has a complexation effect with the tin ion. The complexation effect of the two can enhance the antioxidant properties and radiation resistance of the tin-based perovskite film.
[0080] Comparative Example 2
[0081] Fabrication of tin-based perovskite solar cells. Specifically, the process for fabricating tin-based perovskite solar cells includes operations S1 to S5.
[0082] S1: Provide an ITO transparent glass substrate as the substrate and bottom electrode, and pretreat the ITO transparent glass substrate. Specifically, ultrasonically clean the ITO transparent glass substrate for 20 minutes each with glass cleaner, deionized water, acetone, and isopropanol, dry it in an oven, and then clean it with an ultraviolet ozone generator for 15 minutes.
[0083] S2: Fabrication of the first carrier transport layer. Specifically, PEDOT:PSS is spin-coated onto an ITO transparent glass substrate at a speed of 5000 r / min in air and annealed at 150°C for 15 min; after the PEDOT:PSS film cools, the substrate coated with PEDOT:PSS is transferred into a glove box under a nitrogen atmosphere.
[0084] S3: Prepare the absorber layer. Specifically, prepare 0.8M PEA. 0.15 FA 0.85 SnI 2.85 Br 0.15 A tin-based perovskite precursor solution was prepared, comprising FAI, SnI2, SnF2, and PEABr, wherein the ratio of FAI:SnI2:SnF2:PEABr was 0.85:1:0.075:0.15, and the solvent volume ratio was a DMF (N,N-dimethylformamide)-DMSO (dimethyl sulfoxide) mixed solution with a VDMF:VDMSO ratio of 4:1. The resulting solution was spin-coated onto a hole transport layer at a spin speed of 5000 r / min for 40 s. At the 26th s spin-coating time, 600 μL of Tol (toluene) was added dropwise, and the mixture was annealed at 70 °C for 10 min to obtain a tin-based perovskite film.
[0085] S4: Preparation of the second carrier transport layer ICBA (fullerene derivative). Specifically, a 20 mg / ml ICBA solution was prepared using CB (chlorobenzene) as the solvent; the resulting solution was spin-coated onto a tin-based perovskite absorber layer at a spin speed of 1000 r / min for 30 s, followed by annealing at 70 °C for 10 min to obtain the ICBA electron transport layer; a 5 nm thick BCP (bath copper ether) was formed using a thermal evaporation process.
[0086] S5: Fabrication of the top electrode. A 100 nm thick silver layer was formed using a thermal evaporation process.
[0087] The performance of the tin-based perovskite solar cell prepared in Comparative Example 2 was tested, and the test results are shown in Table 2.
[0088] Example 2
[0089] Tin-based perovskite solar cells were prepared using the same method as in Comparative Example 2, except that the tin-based perovskite precursor solution also included Sn(SCN)2, and the molar ratio of tin ions in Sn(SCN)2 to tin ions in the tin-based perovskite precursor solution was 10%. The performance of the tin-based perovskite solar cells prepared in Example 2 was tested, and the test results are shown in Table 2.
[0090] Example 3
[0091] Tin-based perovskite solar cells were prepared using the same method as in Example 2, except that the molar ratio of tin ions in Sn(SCN)2 to tin ions in the tin-based perovskite precursor solution was 15%. The performance of the tin-based perovskite solar cells prepared in Example 3 was tested, and the test results are shown in Table 2.
[0092] Example 4
[0093] Tin-based perovskite solar cells were prepared using the same method as in Example 2, except that the molar ratio of tin ions in Sn(SCN)2 to tin ions in the tin-based perovskite precursor solution was 20%. The performance of the tin-based perovskite solar cells prepared in Example 4 was tested, and the test results are shown in Table 2.
[0094] Table 2
[0095]
[0096] Figure 9 This is a comparison chart showing the photoelectric conversion efficiency test results of the tin-based perovskite solar cells provided in Comparative Example 2 and Example 2 of the present invention.
[0097] refer to Figure 9 As shown, the normalized power conversion efficiency (PCE) of the tin-based perovskite solar cell in Example 2 of this invention reached 12.01%, and the short-circuit current (Jsc) was 19.33 mA / cm². 2 The open-circuit voltage (Voc) is 0.86V, and the fill factor (FF) is 72.22%. In contrast, the normalized power conversion efficiency (PCE) of the tin-based perovskite solar cell in Comparative Example 2 is only 10.90%, and the short-circuit current (Jsc) is 18.27mA / cm². 2The open-circuit voltage (Voc) was 0.82V and the fill factor (FF) was 72.73%. This fully demonstrates that the addition of the stannous compound stannous thiocyanate has an enhancing effect on the photoelectric performance of tin-based perovskite solar cells.
[0098] Figure 10 This is a comparison chart showing the stability test results of the tin-based perovskite solar cells provided in Comparative Example 2 and Example 2 of the present invention.
[0099] refer to Figure 10 As shown, stability tests indicate that the tin-based perovskite solar cell of Example 2 of this invention exhibits almost no performance degradation after 900 hours, while the tin-based perovskite solar cell of Comparative Example 2 degrades to 85% of its initial performance after only about 320 hours. This fully demonstrates that the solar cell prepared by adding the tin-based perovskite thin film containing the tin thiocyanate compound has higher stability.
[0100] Figure 11 The graph shows a comparison of the photoelectric conversion efficiency test results of the tin-based perovskite solar cells provided in Comparative Example 2 and Examples 2-4 of the present invention.
[0101] Refer to Table 2 and Figure 11 As shown, according to the comparative examples and embodiments of the present invention, by adjusting the raw materials and their proportions in the tin-based precursor solution, it is possible to obtain tin-based perovskite thin films with better film quality and tin-based perovskite solar cells with better photoelectric conversion efficiency.
[0102] Compared to Comparative Example 1, which did not add stannous thiocyanate, Example 1 used stannous thiocyanate to prepare a tin-based perovskite precursor solution, resulting in a tin-based perovskite film with better oxidation resistance and radiation resistance.
[0103] Compared to Comparative Example 2, which did not add stannous thiocyanate, Example 2 used stannous thiocyanate to prepare a tin-based perovskite precursor solution and applied the prepared tin-based perovskite thin film to tin-based perovskite solar cells, resulting in tin-based perovskite solar cells with better photoelectric conversion efficiency and stability.
[0104] It is worth mentioning that, through the comparison of Examples 2 to 4, it can be seen that the main difference lies in the content of stannous thiocyanate, a stannous compound. The photoelectric conversion efficiency of the tin-based perovskite solar cell prepared in Example 2 is better than that in Examples 3 to 4. It can be seen that a molar ratio of 10% between the tin ion content of stannous thiocyanate and the tin ion content in the tin-based perovskite precursor solution is more preferred.
[0105] The use of ordinal numbers such as "first," "second," "third," etc., in the specification and claims to modify the corresponding elements does not imply that the element has any ordinal number, nor does it represent the order of one element with another element, or the order of manufacturing methods. The use of these ordinal numbers is only to enable a named element to be clearly distinguished from another element with the same name.
[0106] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above descriptions are merely specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a tin-based perovskite thin film, characterized in that, include: Tin-based perovskite powder was dissolved in an organic solvent to prepare a tin-based perovskite precursor solution, wherein the tin-based perovskite powder contained tin-containing compounds. as well as A tin-based perovskite precursor solution was coated to form a film, which was then annealed to obtain a tin-based perovskite thin film.
2. The preparation method according to claim 1, characterized in that, The stannous compound includes at least one of stannous thiocyanate, stannous sulfate, stannous oxalate, stannous acetate, stannous sulfide, stannous fluoroborate, stannous petrolate, and stannous octoate.
3. The preparation method according to claim 1, characterized in that, The molar ratio of tin in the tin-containing compound to tin in the tin-based perovskite precursor solution is 0.01% to 10%.
4. The preparation method according to claim 1, characterized in that, Dissolving tin-based perovskite powder in organic solvents includes: Tin-based perovskite powder containing tin compounds was dissolved in an organic solvent at a temperature of 15~70℃.
5. The preparation method according to claim 1, characterized in that, The tin-based perovskite powder also includes formamidinium hydroiodate, stannous iodide, stannous fluoride, and phenylethylamine bromide.
6. The preparation method according to claim 1, characterized in that, The organic solvent includes at least one of dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, and γ-butyrolactone.
7. The preparation method according to claim 1, characterized in that, The methods of coating to form a film include spin coating, blade coating, or spray coating.
8. The preparation method according to claim 1, characterized in that, The annealing temperature for the annealing process is 70℃~100℃.
9. A tin-based perovskite thin film obtained by the preparation method according to any one of claims 1 to 8.
10. A tin-based perovskite solar cell, characterized in that, It includes a light-absorbing layer, which comprises the tin-based perovskite thin film as described in claim 9.
